Reaching Women through Health Information Technology: The Gabby Preconception Care System. Issue 3 (January 2013) - Gardiner, Paula; Hempstead, Megan B.; Ring, Lazlo; Bickmore, Timothy; Yinusa-Nyahkoon, Leanne; Tran, Huong; Paasche-Orlow, Michael; Damus, Karla; Jack, Brian
Purpose: The Centers for Disease Control and Prevention have endorsed the concept of preconception care (PCC). New tools must be developed to promote PCC. Design: Development and testing of a health information technology system to provide PCC. Setting: An urban safety net hospital and an urban university. Subjects: Community recruitment of 31 women in focus groups and 15 women participating in observed usability testing; 9 students recruited from the Office of Minority Health Preconception Peer Educators program participated in pilot testing for 2 months. Intervention: Online interactive animated character ("Gabby") designed to identify and modify preconception risks. Measures: Qualitative transcripts, preconception risk assessment, server data for system usage, self-administered satisfaction surveys, and follow-up phone calls. Analysis: Descriptive statistics of subjects' demographics, satisfaction, PCC risks, and system usage. Transcripts coded using NVIVO. Results: Subjects (n = 24) reported an average of 23 preconception risks; in the pilot, 83% of risks added to the "My Health To-Do List" were addressed by the subject. Seventy-three percent of risks identified as contemplative progressed to action or maintenance. Differences were noted in effectiveness of the system based on initial stage of change for each risk. Conclusion: Results suggest that the PCC system could be effective in influencing positive behavior change. Adding stage of change–focused functionality might have added benefits. This system has great potential to assist in the delivery of PCC.